ヤベオオツノジカの角の形態について ―個体発生に基づく再検討― - 樽野, 博幸; 296; タルノ, ヒロユキ; 奥村, 潔; 1073; オクムラ, キヨシ; 石田, 克; 1074; イシダ, シノグ; Taruno, Hiroyuki; 298; Okumura, Kiyoshi; et al. (大阪市立自然史博物館, 2019)
ヤベオオツノジカ（Sinomegaceros yabei）は，オオツノジカ類の中でもアイルランド産のギガンテウスオオツノジカ（Megaloceros giganteus）と同等の体格を持つ大型種である．しかし，ヤベオオツノジカの完全な形をとどめた角化石は，これまでに1対しか発見されていない．この標本はオオツノジカ類としては小型のものであるが，それが本種の特徴と捉えられてきた．しかし，シカ類の角は年齢により大きくその形態を変えることはよく知られている．本稿では，現生のニホンジカとヘラジカでの研究例を参考に，日本各地から産出したヤベオオツノジカの成長に伴う角の形態変化について考察した．その結果，ヤベオオツノジカの角は，成長に伴い，眉枝や主幹掌状部が広く，主幹柱状部が太くなると共に，指状突起の本数が増え，最も体力が盛んな年齢では，かなり雄大な角を持つことが明らかになった．そして老齢の個体では，眉枝と主幹掌状部は狭くなり，指状突起 は減少すること，主幹柱状部はやや細くなることが明らかになった．また，ヤベオオツノジカにおける主幹掌状部と眉枝の識別点についても論じた．そしてヤベオオツノジカの種の特徴を，角の形態に基づき再定義した．付録1および2では，大阪市立自然史博物館において復元・展示されている，熊石洞標本に基づく復元全身骨格と，生体復元像について，それらの基になった標本を示し，復元当時の見解に言及した． The Yabe’s giant deer （Sinomegaceros yabei） was one of the largest species among the tribe Megacerini, and had nearly the same body size as the“ Irish Elk”（ Megaloceros giganteus）. Tomioka specimen is only one completely preserved antler of S. yabei, and is small. Previously, having the small antler had been regarded as one of the diagnostic characters of S. yabei. However, the morphology of the deer’s antler changes with ontogeny. We examine the ontogenetic variation of the antlers of S. yabei reported from all over Japan by referring to those of the extant sika deer（ Cervus nippon） and moose（ Alces alces）. It becomes clear that, as growing up, the brow tin and main palmation became larger, the main beam became thicker, and the digit increased in number. In the prime of their lives, S. yabei had rather grand antlers. After arriving at senescence, the brow tin and main palmation became smaller, the main beam decreased in thickness, and the digit decreased in number. As a result, these changes are recognized as a part of ontogenetic variation. Also in this paper, the authors present morphological features by which we distinguish the brow tin and main palmation of S. yabei and the emended specific diagnoses of S. yabei based on the antler morphology. In appendeces, a skeleton of S. yabei with the specimens from Kumaishido-cave and its life restoration, which are displayed in the Osaka Museum of the Natural History, ...